Clonal Propagation of Tylophora Indica - An Important Medical Plant Through Tissue Culture - Nadha, Harleen Kaur (My University, 2007)
The present investigation was carried out on an important medicinal plant Tylophora indica belonging to the family Asclepiadaceae. The different vegetative parts i.e. stem, leaf and shoot apices & nodal explants were excised from an elite field grown mature plant and thereafter planted on variously supplemented Murashige and Skoog’s medium for callus induction, organagenesis and multiple shoot proliferation. Tylophora exhibited high degree of multiple shoot proliferation from nodal segments taken from in vivo plants. Prolific multiple shoot regeneration from nodal explants was observed on MS medium + BAP (1-4ppm), MS + BAP (1- 4ppm) + CM (15%). Best results were however obtained on 2ppm BAP, where 45-50 shoots were obtained after 7-8 weeks of culturing. With increase in the concentration of BAP number of shoots formed had waned. Shoots thus obtained were excised & planted on MS medium supplemented with IBA & IAA for induction of roots. Best results were however obtained on MS supplemented with IBA (4ppm). Callus formation occurred from nodal segments, leaf and stem explants (internodal segments) when planted on different combinations of auxins & cytokinins. Murashiege & Skoog’s agar gelled medium supplemented with NAA (4ppm) + K (1ppm) turned out to be optimal for initiation & sustained growth of calli from all the three parts. Callus was also obtained on 2,4-D (4ppm) + Kinetin (1ppm) and BAP (1-6ppm) but time taken for its formation was quite long. The calli thus formed were green, solid & fast growing. The calli induced from different parts on the same medium were more or less identical in morphology. The calli obtained were heterogenous being composed of parenchymatous ovoid, oblong, semicircular cells or those with aberrant shapes. The spectrum of induced differentiation from calli was wide and involved xylogenesis, rhizogenesis and caulogenesis. The trachieds occurred either singly or were grouped together as nodules. They had sclariform thickenings on their walls. Root formation occurred after 3 weeks when callus was planted on MS medium supplemented with different concentrations of IBA (0.5-4ppm). Roots obtained were long, white, and branched. Shoot formation from callus was obtained on MS + BAP (0.5-4ppm). Nearly 5-8 shoots were obtained after 4 weeks of culturing. Shoots thus obtained were rooted on a separate root inducing media consisting of different concentrations of IBA but best results were obtained on MS + IBA (4ppm). The plantlets with elongated root and shoot system were then subjected to hardening and attempts were made to establish these plantlets into the soil.
Keywords: Tylophora Indica; Clonal Propagation